Предмет: Алгебра,
автор: S5um1meroshka
упростите выражение (b+1/b-1 - b/b+1)/3b+1/2b-2
Ответы
Автор ответа:
0
)))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))))
Приложения:
Автор ответа:
0
1)(b+1)/(b-1)-b/(b+1)=(b²+2b+1-b²+b)/(b²-1)=(3b+1)(b²-1)
2)(3b+1)/(b²-1):(3b+1)/(2b-2)=(3b+1)/[(b-1)(b+1)]*2(b-1)/(3b+1)=2/(b+1)
2)(3b+1)/(b²-1):(3b+1)/(2b-2)=(3b+1)/[(b-1)(b+1)]*2(b-1)/(3b+1)=2/(b+1)
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: tanapozdina1001
Предмет: География,
автор: sumkovaserafima2
Предмет: Математика,
автор: karokolu
Предмет: Математика,
автор: sddsgfmiuaewlkjfvhu
Предмет: Математика,
автор: Kate167